The genus Scirtothrips Shull (Insecta, Thysanoptera, Thripidae) and three related genera in Japan - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2007)
The genus Scirtothrips and related genera in Japan were studied, and the following four genera and eight species recorded: Anascirtothrips okinawanus n. sp., Drepanothrips reuteri Uzel, Scirtothrips albidus n. sp., S. dorsalis Hood, S. flavus n. sp., S. katsura n. sp. and S. machili n. sp., Parascirtothrips fagaceae n. gen. et sp. The male of D. reuteri is recorded from Japan for the first time. Ten genera are recognized in the Scirtothrips genus group, and relationships between these are discussed.